2019
DOI: 10.1002/adfm.201904810
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Two‐Dimensional Tin(II) Iodide Hybrid Organic–Inorganic Perovskite Based on Stilbene Derivative

Abstract: Hybrid organic-inorganic perovskites have recently emerged as potential disruptive photovoltaic technology. However, the toxicity of lead used in state-of-the-art hybrid perovskites solar cell prevents large-scale commercialization, which calls for lead-free alternatives. Sn-based perovskites have been considered as alternatives but they are limited by rapid oxidation and decomposition in ambient air. Here, an Sn-based two-dimensional hybrid organic-inorganic perovskites [A 2 B (n-1) Sn n I (3n+1) ] (n = 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 36 publications
2
78
0
Order By: Relevance
“…[ 125 ] However, LD tin‐based perovskites on different additives and reducing agents have commanded less research, allowing for more explorations on their applications. [ 119 ] Meanwhile, the development of new LD materials, such as (2‐(4‐(3‐fluoro)stilbenyl) ethanammonium iodide (FSAI)), [ 135 ] is another strategy to further improve their performance in the future. Finally, there are a few studies on Dion–Jacobson and interlayer space in tin‐based PSCs, pointing us to a new development path. Exploring compact inorganic transport layer.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…[ 125 ] However, LD tin‐based perovskites on different additives and reducing agents have commanded less research, allowing for more explorations on their applications. [ 119 ] Meanwhile, the development of new LD materials, such as (2‐(4‐(3‐fluoro)stilbenyl) ethanammonium iodide (FSAI)), [ 135 ] is another strategy to further improve their performance in the future. Finally, there are a few studies on Dion–Jacobson and interlayer space in tin‐based PSCs, pointing us to a new development path. Exploring compact inorganic transport layer.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…Moreover, as shown in Figure f, a coaddition of pyrazine and SnF 2 can effectively subdue surface phase separation leading to a more homogenous film . Functionalized organic chains such as that of 2‐(4‐(3‐fluoro)stilbenyl)ethanammonium iodide (FSAI) can also ensure moisture resistance and strong cohesive bonding interactions in the 2D structure . Overall, SnF 2 is the most widely used additive in Sn halide perovskite preparation.…”
Section: Additives For Sn Halide Perovskite Filmsmentioning
confidence: 99%
“…In this case, Sn‐based 2D perovskites have been identified as suitable alternatives, while they are still hindered by the instability in the air environment. [ 50 ] Loh et al [ 51 ] reported a Sn‐based hybrid organic–inorganic 2D perovskite of (FSA) 2 SnI 4 with enhanced air stability, using 2‐(4‐(3‐fluoro)stilbenyl)ethanammonium (FSA + ) as the organic cations. The water instability of (FSA) 2 SnI 4 perovskite is ascribed to the water resistance of fluorinated organic chains, as a concrete effect of strongly cohesive bonding contained the H bonding, CH‐X type of H bonding, weak interlayer of F‐F interactions, and weak aspectant type of π‐π interaction.…”
Section: Synthesis Structure and Physical Properties Of 2d Metal‐hamentioning
confidence: 99%